Electric vehicle charging station components and current scenario - Wahsh, Said; Mariah, Ibrahim; Nashed, Maged N. F. (Institute of Advanced Engineering and Science, 2024)
Since the range of an electric vehicle (EV) is important, vehicles with the longest range are preferred. As a result, a survey is conducted on the longest-range vehicles commercially available to estimate the charging power required. EV range has recently increased significantly and can now be charged at home, adding to the benefits of EV. The paper will present the best three EV models with the longest range. So, the specifications of the most popular EV commercially available had been analyzed. Nonetheless, charging stations are still required, which is a critical issue. This paper discusses various approaches to EV charging stations that rely primarily on AC or DC power supply. The previous year’s accomplishments will be highlighted. The three EV charging station levels will be thoroughly addressed. It is primarily classified based on voltage, power and types. In this type of charging EV must equipped with rectifier to change AC-DC to charge batteries. The impact of rapid advancements in power electronics technology has been discussed as AC-DC converter, as its advancement will determine the future of EV charging stations. Renewable energy sources (hydropower, photovoltaic, and wind) are now essential as energy source. Recommendations for increasing EV sales will be made.